Group Peer Teaching: A Strategy for Building Confidence in Communication and Teamwork Skills in Physical Therapy Students. Issue 3 (2016) - Seenan, Christopher; Shanmugam, Sivaramkumar; Stewart, Jennie
Abstract : Background. : First‐year entry‐level students are faced with a number of challenges including social and cultural changes when enrolling in a university. Building confidence in their skills of academic study can help minimize the impact of this transition and prepare students to maximize learning. Aim. : To embed reciprocal peer teaching (RPT) within the physical therapy curriculum and explore its effects on student confidence in communication and teamworking skills. Methods. : Fifty‐seven first‐year entrylevel physical therapist (PT) students completed group peer teaching embedded in a core first‐year anatomy module. Questionnaire, focus groups, and semistructured interviews were used to evaluate the outcome of this novel learning and teaching strategy. Results. : Students reported satisfaction with the experience of the group peer teaching. The key themes were group work, peer teaching, and peer feedback. Students also reported increased confidence in skills, especially in communication and teamwork. Faculty felt that the group peer teaching was beneficial for students, and an effective learning and teaching strategy. Conclusion. : This study found that RPT embedded within a first‐year course helped increase skills and confidence in communication and teamwork. Peer teaching appears to be an effective method in aiding the development of important skills within the first year of a PT education program.